Association of Lumbar Paraspinal Muscle Morphometry with Degenerative Spondylolisthesis - Lee, Eun Taek (Int J Environ Res Public Health, 2021)
The objective of this study was to assess the cross-sectional areas (CSA) of lumbar paraspinal muscles and their fatty degeneration in adults with degenerative lumbar spondylolisthesis (DLS) diagnosed with chronic radiculopathy, compare them with those of the same age- and sex-related groups with radiculopathy, and evaluate their correlations and the changes observed on magnetic resonance imaging (MRI). This retrospective study included 62 female patients aged 65–85 years, who were diagnosed with lumbar polyradiculopathy. The patients were divided into two groups: 30 patients with spondylolisthesis and 32 patients without spondylolisthesis. We calculated the CSA and fatty degeneration of the erector spinae (ES) and multifidus (MF) on axial T2-weighted magnetic resonance (MR) images from the inferior end plate of the L4 vertebral body levels. The functional CSA (FCSA): CSA ratio, skeletal muscle index (SMI), and MF CSA: ES CSA ratio were calculated and compared between the two groups using an independent t-test. We performed logistic regression analysis using spondylolisthesis as the dependent variable and SMI, FCSA, rFCSA, fat infiltration rate as independent variables. The result showed more fat infiltration of MF in patients with DLS (56.33 vs. 44.66%; p = 0.001). The mean FCSA (783.33 vs. 666.22 mm(2); p = 0.028) of ES muscle was a statistically larger in the patients with DLS. The ES FCSA / total CSA was an independent predictor of lumbar spondylolisthesis (odd ratio =1.092, p = 0.016), while the MF FCSA / total CSA was an independent protective factor (odd ratio =0.898, p = 0.002)